Artificial Polysialic Acid Chains as Sialidase-Resistant Molecular-Anchors to Accumulate Particles on Neutrophil Extracellular Traps - Galuska, Christina E.; Dambon, Jan A.; Kühnle, Andrea; Bornhöfft, Kim F.; Prem, Gerlinde; Zlatina, Kristina; Lütteke, Thomas; Galuska, Sebastian P. (Frontiers in Immunology, 2017)
Neutrophils are involved in numerous immunological events. One mechanism of neutrophils to combat pathogens is the formation of neutrophil extracellular traps (NETs). Thereby, neutrophils use DNA fibers to form a meshwork of DNA and histones as well as several antimicrobial components to trap and kill invaders. However, the formation of NETs can lead to pathological conditions triggering among other things (e.g. sepsis or acute lung failure), which is mainly a consequence of the cytotoxic characteristics of accumulated extracellular histones. Interestingly, the carbohydrate polysialic acid represents a naturally occurring antagonist of the cytotoxic properties of extracellular histones. Inspired by polysialylated vesicles, we developed polysialylated nanoparticles. Since sialidases are frequently present in areas of NET formation, we protected the sensitive non-reducing end of these homopolymers. To this end, the terminal sialic acid residue of the non-reducing end was oxidized and directly coupled to nanoparticles. The covalently linked sialidase resistant polysialic acid chains are still able to neutralize histone mediated cytotoxicity and to initiate binding of these polysialylated particles to NET filaments. Furthermore, polysialylated fluorescent microspheres can be used as a bioanalytical tool to stain NET fibers. Thus, polySia chains might not only be a useful agent to reduce histone mediated cytotoxicity but also an anchor to accumulate nanoparticles loaded with active substances in areas of NET formation.